Mystik und Befreiung. Dorothee Sölles Verständnis des Glaubens als riskanter Lebensform - König, Katrin (epd-Dokumentation)

Verborgene Gegenwart. Simone Weils existenzphilosophische Deutung der in Abwesenheit anwesenden Gottesliebe - Koenig, Katrin (Neue Zeitschrift für Systematische Theologie und Religionsphilosophie)
Zusammenfassung Wie kann Gottes Gegenwart trotz ihrer Verborgenheit wahrgenommen werden? In dem folgenden Beitrag möchte ich zeigen, wie Simone Weil die Erfahrungen der Verborgenheit und der Abwesenheit Gottes als Signatur des Unglücks und der Entwurzelung der Menschen in der Moderne analysiert. Des Weiteren wird dargestellt, wie Simone Weil vor diesem Hintergrund mit einer kreuzestheologischen Denkfigur reflektiert, wie die Gottesliebe in besonderer Weise im Unglück verborgen anwesend sein kann, trotz Erfahrung der Abwesenheit Gottes. Hier schließt sich die erkenntnistheoretische Frage nach der Wahrnehmbarkeit der verborgenen Gegenwart Gottes an. So soll ausgeführt werden, wie Simone Weil aufzeigt, wie durch ästhetische Formen der Schönheit und Ordnung der Welt, durch ethische Formen von Nächstenliebe und Freundschaft und durch die religiöse Formen in Liturgie und Gebet als höchster Form der Aufmerksamkeit die verborgen gegenwärtige Gottesliebe indirekt wahrgenommen werden kann. Dies spricht schließlich für eine andere Deutung der Verborgenheit Gottes als im sog. Verborgenheitsargument von J. L. Schellenberg, mit dem von der Verborgenheit auf die Nichtexistenz Gottes geschlossen wird.

Confidence regained: Providence and prayer in the works of Catherine of Siena, Anne Conway and Simone Weil - Koenig, Katrin (Scottish Journal of Theology)

Motorische Grundausbildung – ein Praxisbeispiel aus dem Bewegungs-, Spiel-, und Sportlabor (besslab) - Strotmeyer, Anne; Satzinger, Nicole (Wissenstransfer in der Sportpädagogik)

Modeling higher-order social influence using multi-head graph attention autoencoder - Meydani, Elnaz; Duesing, Christoph; Trier, Matthias (Information Systems)

Towards a Model of Polarization Reduction with Recommender Systems - Meydani, Elnaz; Trier, Matthias (Wirtschaftsinformatik)

Transiente Dynamische Analyse – Vergleich zeit- und frequenzdiskreter Auswertemethoden anhand geclinchter Aluminiumverbindungen - Reschke, Gregor; Brosius, Alexander (Werkstoffe und Bauteile auf dem Prüfstand)

Forschungsprojekt WATS up: What About Teacher Shortage. Lehrkräftemangel im internationalen Vergleich - Wüllner, Sabrina; Seeliger, Sandra

Fachbezogene Core Practices in der Lehrkräftebildung am Beispiel des Pädagogikunterrichts - Wüllner, Sabrina; Schellenbach-Zell, Judith; Rochnia, Michael

Bildungsplan Stadtteilschule. Jahrgangsstufen 5-11. Pädagogik - Dube, Alexandra; Jäger, Christina; Knöpfel, Eckehardt; Wüllner, Sabrina

Bildungsplan Gymnasium. Sekundarstufe I. Pädagogik - Dube, Alexandra; Jäger, Christina; Knöpfel, Eckehardt; Wüllner, Sabrina

Direct assessment of the influence of pose repeatability on the accuracy of dimensional measurements for computed tomography systems with high degrees of freedom - Butzhammer, Lorenz; Handke, Niklas; Wittl, Simon; Herl, Gabriel; Hausotte, Tino (Measurement Science and Technology)
Abstract Industrial x-ray computed tomography (CT) systems with high geometric flexibility are increasingly utilized for large-scale measurement objects or challenging measurement tasks. To maintain high accuracy when deviating from the established circular scan trajectory, trajectory calibration methods using multi-sphere reference objects with known marker positions are commonly employed. These multi-sphere objects can either be scanned together with the measurement object (online trajectory calibration) or in a separate scan (offline trajectory calibration). While offline calibration increases machine time, it generally results in higher scan quality. However, a sufficient pose repeatability is necessary to ensure comparable or even superior accuracy to online calibration. In this contribution, we present a straightforward procedure to compare both types of trajectory calibration in a way that the differences of the results can directly be traced back to the influence of the pose repeatability. The multi-sphere reference object is not only used for trajectory calibration, but simultaneously as a measurement object for repeated measurements. The methodology is tested on both a twin robotic CT system and a conventional CT system that is additionally equipped with a hexapod manipulator for adaptive object tilting. Results showed, independent from the type of trajectory calibration, systematic measurement errors in the order of 10 −5 –10 −4 of measured sphere distances and sphericity values below 50 μ m . For sphere distances, random errors were increased by a factor of 5 due to the offline trajectory calibration, but were still low ( < 1 μ m ) in comparison to systematic errors and the spread of different measurement features. Overall, both investigated systems demonstrated sufficient positioning repeatability for offline trajectory calibration. The method is in general also applicable to any other types of manipulator systems used for CT devices. It provides a workflow for the decision which type of trajectory calibration is preferable for a given CT system.

Practical Approaches for Determining the Structural Resolution Capability of X-ray Computed Tomography Measurement Tasks - Busch, Matthias; Hausotte, Tino (Metrology)
The structural resolution describes the ability of a measuring device to detect small structures on the surface of a component or test specimen by means of a quantitative value. However, the structural resolution in the computer tomograph depends on the object and must therefore be determined separately for each measurement task. The previous approaches to structural resolution determination are only related to test specimens. In this paper, less discrete approaches based on a circular pattern are presented, which can be integrated into the measured component. A voxel-based methodology as well as two surface-based methodologies are described. The investigation results regarding the effect of the component position on the structural resolution are obtained on the basis of real CT measurements. A comparison is also completed with the well-known hourglass method. The results show that the resolution depends on the object being measured, with similar values being obtained for the same object using different methods.

Task-specific scan trajectory modification for dimensional X-ray computed Tomography with high throughput - Butzhammer, Lorenz; Hausotte, Tino (tm - Technisches Messen)
Zusammenfassung Eine Erweiterung der Scantrajektorie für die industrielle Röntgen-Computertomographie von einer kreisförmigen Form (entsprechend einer 360°-Rotation des Messobjekts) hin zu frei wählbaren Aufnahmeposen hat das Potenzial, durch eine geeignete Trajektorienanpassung Messabweichungen zu reduzieren. In diesem Beitrag wird eine solche Trajektorienanpassung durch einen Hexapoden als Messobjektmanipulator und eine güteparameterbasierte Methodik zur Wahl einzelner Trajektorienpunkte erreicht. Die Ergebnisse zeigen, dass sich vor allem für eine geringe Projektionszahl signifikante Vorteile ergeben, was vor allem im Hinblick auf Inline-CT mit hohem Durchsatz von Relevanz ist.

Hans Lenk (1985): Die achte Kunst. Leistungssport – Breitensport. Osnabrück: Fromm. - Meier, Heiko (Sport und Gesellschaft)

Boundary Work in Generative AI Platforms: How Platform Providers Manage Complementors’ Changing Role - Mayer, Anne-Sophie; Kostis, Angelos; Strich, Franz; Holmström, Jonny (Academy of Management Proceedings)
Digital platforms increasingly integrate generative AI to dynamically create, optimize and adapt content with the aim to create novel opportunities for platform’s viability. However, the integration of GenAI into digital platforms fundamentally transforms complementors’ role as GenAI is able to autonomously generate content which was previously exclusively performed by complementors. To understand how platforms manage the changing role of complementors in response to AI generated content, we draw from an in-depth qualitative study of a digital learning platform. This empirical case allows us to explore which tensions arise between platform complementors and GenAI’s agency, and how the platform provider engages in different boundary work to manage the changing role of complementors to ensure the platform’s viability. Our study aims to contribute to the literature on GenAI and digital platforms.

The Emergence of Generative AI Platforms: The Changing Role of Complementors in Educational Practices - Mayer, Anne-Sophie; Strich, Franz; Kostis, Angelos; Holmström, Jonny (ECIS 2024 Proceedings)
Generative Artificial Intelligence (GenAI) systems empower platforms to dynamically create, optimize and adapt content promising to create novel benefits for platform’s viability. However, we know little about how the integration of GenAI into digital platforms redefines complementors’ role as a result of GenAI autonomously generating content which was previously exclusively performed by complementors. To understand how platforms can manage the changing role of complementors in response to AI generated content, we draw from an in-depth qualitative study of a digital learning platform. By using a boundary work lens, our empirical case allows us to explore which tension arises between platform complementors and GenAI, and how the platform provider engages in different practices to manage the changing role of complementors to ensure the platform’s viability. Our study aims to contribute to the literature on GenAI and digital platforms.

Charakterisierung des Verformungszustandes gleichartiger Stahl-Stahl-Clinchverbindungen durch Anwendung quantitativer Bildanalyse - Hollmer, Katharina; Kuczyk, Martin; Friedlein, Johannes; Mergheim, Julia; Steinmann, Paul; Zimmermann, Martina

Task-specific scan trajectory modification for dimensional X-ray computed Tomography with high throughput - Butzhammer, Lorenz; Hausotte, Tino (tm - Technisches Messen)

Innovation of the Platform Economy: Key Stakeholders and Starting Points for Sustainable Careers - Hofer, Annabelle; Rivkin, Wladislaw; Strich, Franz; Ihl, Andreas; Mayer, Anne-Sophie; Lei, Xue; Zhou, Lian; Huang, Xinran; Schweitzer, Vera M.; Genz, Sabrina; Gerten, Elisa; Trutwin, Lucas; et al. (Academy of Management Proceedings)
The platform economy introduces novel challenges and opportunities at the intersection of organizational structure, stakeholder relationships, and societal impact (Ashford et al., 2018; Caza et al., 2022; Cropanzano et al., 2023; Fieseler et al., 2019; Kuhn & Maleki, 2017). Following the call for rigorous methodological research on platform workers (Cropanzano et al., 2023), this symposium sheds light on the career development of platform workers by taking central stakeholders (e.g., workers, requesters, platform) into account. The five contributions cover diverse methodological approaches (e.g., longitudinal qualitative interviews, longitudinal quantitative surveys, diary studies), investigating online and offline platform workers from different online labor platforms (OLPs) in Asia, Europe, and the US. We bring together researchers from different fields (e.g., economics, management, psychology). They investigate how platform workers experience working on OLPs and how such experiences shape their careers. The symposium’s contributions collectively deepen our understanding of the platform economy by addressing platform design (cf. presentation [P] #P1, #P2), psychological aspects, such as well-being, linked to the interaction of workers with the requesters (cf. #P3), the decision-making of workers within the platform economy and its link to the gender pay gap (cf. #P4), and by proposing a novel framework of Transactional Careers to better understand the complex career development of platform workers (cf. #P5). This symposium will provide a platform for exchange among scholars from different fields interested in the platform economy to contributes substantial scientific implications for platform workers, policymakers, and OLPs for their important endeavor to develop a sustainable digitalized labor market, considering the role of different stakeholders.